Impact of Surface Modification and Nanoparticle on Sisal Fiber Reinforced Polypropylene Nanocomposites - Idowu David Ibrahim; Tamba Jamiru; Emmanuel Rotimi Sadiku; Williams Kehinde Kupolati; Stephen Chinenyeze Agwuncha (Journal of Nanotechnology)
The use of plant fibers, polymer, and nanoparticles for composite has gained global attention, especially in the packaging, automobile, aviation, building, and construction industries. Nanocomposites materials are currently in use as a replacement for traditional materials due to their superior properties, such as high strength-to-weight ratio, cost effectiveness, and environmental friendliness. Sisal fiber (SF) was treated with 5% NaOH for 2 hours at 70°C. A mixed blend of sisal fiber and recycled polypropylene (rPP) was produced at four different fiber loadings: 10, 20, 30, and 40 wt.%, while nanoclay was added at 1, 3, and 5 wt.%. Maleic anhydride grafted polypropylene (MAPP) was used as the compatibilizer for all composites prepared except the untreated sisal fibers. The characterization results showed that the fiber treatment, addition of MAPP, and nanoclay improved the mechanical properties and thermal stability and reduced water absorption of the SF/rPP nanocomposites. The tensile strength, tensile modulus, and impact strength increased by 32.80, 37.62, and 5.48%, respectively, when compared to the untreated SF/rPP composites. Water absorption was reduced due to the treatment of fiber and the incorporation of MAPP and nanoclay.